Trail of the Spellmans : document #5 - Lutz, Lisa (Lutz, Lisa. Spellman novel., 2013)
For the first time in Spellman history, Isabel Spellman, P.I., might be the most normal member of her family. Yet as a number of cases pile, Izzy won't stop hunting for the answers--even when they threaten to shatter both the business and the family.